Validating an English language teaching reflection inventory in a Chinese EFL context. (April 2015) - Xu, Jinfen; Li, Banban; Curtis, Andy
Abstract: The present study aims to validate Akbari et al.'s (2010) English Language Teaching Reflection Inventory in a Chinese EFL context. It comprises two phases. During the first phase, Akbari et al.'s (2010) hypothetical model was modified and validated through exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). The data used in this phase includes two samples (S1 = 334 and S2 = 1055), making a total of 1389 EFL teachers from 16 different universities or colleges in China. The EFA was carried out with the first sample, and the CFA was carried out with both the first and second samples. During the second phase, the data from the second sample was used to investigate the surveyed participants' reflective practices. To gain a deeper understanding of their practices, 12 teachers were interviewed. The analysis of the data revealed the following outcomes and conclusions: (1) Akbari et al.'s original six-factor model with 42 items was modified and a new seven-factor model with 33 items was developed; (2) The Chinese EFL teachers' reflection in this study was found to be at a medium level. The "classroom management" and "moral" factors were found to be the most frequently reflected on, and the "critical" and the "practice" factors were the least. Suggestions for future research on teachers' reflective practices are also offered.